PERLINDUNGAN NORMA PENGUPAHAN DALAM PERSPEKTIF KEJAHATAN KORPORASI - Santosa, Andry (Magister Ilmu Hukum Sekolah Pascasarjana Unida, 2015)
This study aims to determine how the protection of wage norms and also what kind of offenses committed by employers and how the efforts to resolve it. Corporate responsibility in the field of protection of wage norm of cases of criminal acts that violate the provisions of paying wages below the Provincial Minimum Wage (UMP) or Minimum Wage Regency / City (MSE) was only applied to the organs of the management corporation (company), like leadership company (Director) who carries on business in the corporate everyday. This shows that corporate criminal responsibility in the field of wage protection can not be applied so that the need to change the attitude of the judiciary that the corporation may also be responsible for acts committed by the corporation itself persoon. Given the existing criminal provisions in employment in the form of sanctions of imprisonment and / or fines.